Images of the disciplining of psychology, 1890–1940. Issue 2 (3rd July 2018) - Green, Christopher D.
ABSTRACT: Over the course of psychology's first several decades, the language used to convey the subject matter gradually shifted from being free and literary to being strictly constrained and disciplined by increasingly focused theoretical demands. The project described here, "Disciplining Psychology, " aimed to depict this transformation by generating images of the faces of three highly influential psychologists—William James, Sigmund Freud, and B. F. Skinner. Each image is composed of the words used in one of each individual's most important books. The tightening of the disciplinary vocabulary is revealed in the differences among the three arrays of words themselves, but I have also striven to reflect it in the aesthetic aspects of each image. The method used here could easily be extended to a wider array of authors, texts, and psychological topics.